Effect of Border Environment on Trade and Political Relations of Indo-China: Examining the Impact of Border Tensions on Trade and Politics in Indo-China (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This study investigates how border tensions between China and India have  affected  the economic relationship  and the  political  partnership between these two countries over the last 50 years. China and India have been at odds over their borders since the initial  establishment of  the McMahon line in 1914. Since the Indo-China War in 1962, mistrust and disputes regarding the actual border have reigned, seemingly affecting the relationship  at all  levels. In  spite  of enduring political tensions,  an economic  relationship  has blossomed to  the point that  China  is now India’s largest trading partner. While bilateral trade is expected to top US$60  billion in  2010-11  ending  March 31,  according to  latest official estimates, and is likely to continue to increase, the border issue remains virtually unchanged from 50 years ago. Although economically lucrative Indo-Chinarelations are  riper  for competition than cooperation,  theborder dispute has become increasingly problematic for both parties.